MENTAL HEALTH ORIENTATION, PSYCHOLOGICAL CHALLENGES, PERSONALITY TRAITS, AND COPING STRATEGIES AMONG NURSES IN THE NEW NORMAL (Proceedings of the International Conference on Social Sciences, 2023)
This study developed a causal model of the nurses' mental health orientation, psychological challenges, personality traits, and coping strategies in the new normal. The descriptive-correlational and causal-comparative research designs were employed using a modified researcher-made survey instrument with content validity and reliability established. It was conducted in the province of Bukidnon. Data collection using the questionnaires was tabulated, examined, and interpreted. The findings indicated that PWBI and DASS21 were insignificant; however, personality traits neuroticism that co-varies with openness to experience: conscientiousness, extraversion, and agreeableness, measured high significance in predicting coping strategies among nurses during the new normal. Causal models 1,2, and 3 found variables of personality trait significant; however, model 4 best fits the coping mechanisms of nurses in the new normal because all of the indices match the criteria of the model, validating that Model 4 is a good fit. The conclusion suggests the need for profound awareness of mental health, psychological perception, personal character development, and coping strategies enhancement among nurses to become practical, efficient, resilient, and productive in their respective institutions and the community
Keywords: openness to experience, conscientiousness, extraversion, agreeableness, neuroticism